Про одну систему з повторними викликами і ненадійним приладом - Лебєдєв, Є.О.; Шарапов, М.М.; Лівінська, Г.В. (Доповіді НАН України, 2020)
Розглядається модель системи з повторними викликами і одним ненадійним приладом. Процес обслуговування в системі задається двовимірним ланцюгом Маркова. Перша компонента вказує на число джерел повторних викликів, а друга фіксує стан приладу у поточний момент часу: зайнятий обслуговуванням, вільний
і готовий до обслуговування, вийшов з ладу і відновлюється. Головною особливістю системи, що розглядається, є те, що інтенсивність вхідного потоку залежить від величини черги повторних викликів.
Для процесу обслуговування знайдено умову існування стаціонарного режиму та векторно-матричні
формули, які подають стаціонарні імовірності через параметри моделі у явному вигляді. Для контролю
точності обчислень за цими формулами отримана оцінка залишку ряду, який задає нормуючу сталу. У випадку, коли вхідний потік є пуассонівським, для нормуючої сталої отримано точний вираз. Застосування
отриманих результатів продемонстровано на числових прикладах, у яких наведена залежність блокуючої
ймовірності в стаціонарному режимі від параметрів системи. We consider a model of retrial queue with one unreliable server whose lifetime is an exponentially distributed
random variable with the known failure rate. A two-dimensional Markov chain defines the service process in
the system. Its first component indicates the number of sources of repeated calls, and the second one fixes the
status of the server at the current time: the server is busy, free, and ready for maintenance or out of order.
The main feature of the considered system is that the input flow rate depends on the size of the queue of repeated
calls. Each of the sources of repeated calls can generate a call with the same rate. If a primary or repeated call
arrives into the system and finds the server idle, its service begins immediately. If the server is busy, the call is
directed to the orbit and becomes a source of retrial calls.
For the service process, a condition for the existence of a stationary regime and vector-matrix formulas
are found. These formulas express stationary probabilities through the model parameters in the explicit form. To
control the accuracy of calculations using these formulas, an estimate of the remainder of the series is obtained,
which sets the normalizing constant. The rate of the remainder decreasing to zero has an exponential upper
estimation. In the case where the input flow is the Poisson one, the exact expression is obtained for a normalizing
constant. The application of the obtained results is demonstrated by numerical examples, which show
the dependence of the blocking probability in the stationary regime on the parameters of the system. The obtained
results can be used to solve optimization problems in the class of threshold strategies.